Enhancing security and privacy in local area network (LAN) with TORVPN using raspberry PI as access point: a design and implementation / Mohd Nizam Osman ... [et al.] - Osman, Mohd Nizam; Sedek, Khairul Anwar; Othman, Nor Arzami; Rosli, Muhammad Afiqhakimi; Maghribi, Mushahadah (UiTM Cawangan Perlis, 2021)
Network security is designed to protect the integrity, confidentiality and accessibility of computer networks and data using both software and hardware technologies. Every person, including organization requires a degree of network security solutions in place to protect it from the ever-growing landscape of cyber threats in the wild today. This paper aims to design and implement TorVPN as an access point using Raspberry Pi in enhancing security and privacy in Local Area Network (LAN). This access point was implemented by using the combination of The Onion Router (Tor) and Virtual Private Network (VPN) services. Then, the graphical user interface application was developed to assist and facilitate the user to access the network securely without having the difficulties to configure and install any software. To determine the effectiveness of the proposed work, there were two experiments involved in this study. Firstly, the confidentiality test which to verify its privacy in keeping the information securely. Secondly, the performance test of the Internet connectivity in terms of ping, download and upload speed. The encourage results was expected as the confidentiality tested on the TorVPN access point network has shown the positive outcome by securing client’s Internet data packet. While, the Internet connectivity is not stable enough, when the client’s IP address changed in the network. Hence, the combination VPN and Tor service using Raspberry Pi as an access point inside the LAN is suitable and secure the information in the network, but do not suggest for user who wants a good Internet connectivity.